Health Policy Development in Flemish Small-Sized Municipalities: A Real-World Intervention. Issue 5 (September 2016) - De Cocker, Katrien; Dubuy, Veerle; De Bourdeaudhuij, Ilse; Maes, Lea; Seghers, Jan; Lefevre, Johan; De Martelaer, Kristine; Buytaert, Bruno; Cardon, Greet
Background. A health promotion institute developed an intervention to support small-sized municipalities (<15, 000 citizens; n = 167) in their development of a local health policy. Objectives. To (1) find out which municipalities showed interest to participate and (2) assess the intervention effects after 1 year. Method. The intervention consisted of (1) completing an online tool that generated feedback on the quality level of the health policy (9 scores) and (2) receiving advice (four contacts) from the local-regional support service for health promotion. In total 121 small-sized municipalities agreed to participate (intervention municipalities), and the nonparticipating municipalities (n = 46) were used as a comparison group. Chi-square tests were conducted to compare baseline quality scores between intervention and comparison municipalities and to assess the change (baseline to follow-up) within the intervention group. Results. At baseline, intervention municipalities had significant higher health policy quality scores compared to the comparison municipalities. Municipalities interested in the intervention mostly had already high policy scores. A significant positive shift in the quality levels was found after 1 year in the intervention municipalities. Conclusion. The intervention succeeded in improving the quality levels of the local health policy, though municipalities scoring low and possibly benefiting most from the intervention need to be extra-motivated to participate.